Iron deficiency anemia among hospitalized children in a rural teaching hospital: a cross sectional study - Santokh, Inderpreet; Gaur, Bablu Kumar; Narayan, Raghvendra; Maini, Baljeet; Bharadwaj, A. K. (International Journal of Contemporary Pediatrics, 2018)
Background: Iron deficiency anemia is the most common nutritional deficiency disorder in the world. The present study was conducted to know the prevalence and severity of iron deficiency anemia among of 6 months to 60 months old children. A large proportion of iron deficiency is preventable with appropriate and timely intervention. Methods: This cross-sectional study was done on 100 children clinically suggestive of anemia with hemoglobin level less than 11gm/dl admitted in pediatrics ward of tertiary care hospital. 5 ml of blood sample was taken and complete hemogram, peripheral blood film and serum ferritin estimation was done. Case were studied in reference to history, age, clinical examination, hemoglobin level and confirmation of iron deficiency anemia was done by serum ferritin levels. Results: The prevalence of iron deficiency anemia in present study was 56%. It was most prevalent in the age group of 6 to 24 months. Exclusively breastfed children showed higher prevalence of iron deficiency anemia in present study, however no statistical correlation was found. Low Serum ferritin levels have statistically significant result with socioeconomic status, with as many as 69.4% suffering from iron deficiency anemia belonging to low socioeconomic status. Conclusions: Prevalence of iron deficiency anemia remains alarmingly high and major health problem in our country. All anemia are not iron deficiency anemia. Low socioeconomic status is a huge hurdle in child health and greatly influences prevalence of iron deficiency anemia. Serum ferritin is a most sensitive marker of iron deficiency anemia, helps diagnose it early in its course, which can be missed on clinical or routine blood investigations.